The Loose Ends List - Firestone, Carrie (New York, 2016)
"Seventeen-year-old Maddie ONeill Levine and her zany family accompany their terminally ill matriarch on her death with dignity cruise, where Maddie falls in love, makes new friends, and struggles to find the strength to let go of her beloved Gram"--
Keywords: Family life -- Fiction; Death -- Fiction; Cruise ships -- Fiction; Grief -- Fiction